Analisis Prediksi Kebangkrutan Dengan Metode Grover Pada PT. Garuda Indonesia Tbk - Astri Ramadhani (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to find out and analyze profitability and liquidity ratios in assessing financial performance at PT. Adaro Energy, Tbk. This type of descriptive research uses a list of tables of financial statements, balance sheets and profit and loss at PT. Adaro Energi, Tbk as a research instrument. The population used in this study is the entire financial statements of PT. Adaro Energi, Tbk since being listed on the IDX from 2008 to 2021, namely for 13 years. The sample in this study is the financial statements of PT. Adaro Energi, Tbk for 10 years, from 2012 to 2021. The sampling technique used in this research is purposive sampling technique. Data collection techniques in this study are documentation and literature study. Descriptive analysis in this study is analysis of data per component of financial ratios used to assess financial performance consisting of profitability ratios as measured by Return On Assets (ROA) and Gross Profit Margin (GPM) and liquidity ratios as measured by Quick Ratio (QR). ) and Net Working Capital (NWC). Statistical analysis used one-party t-test (One Sample t-test). The results of the research show the financial performance of PT. Adaro Energi, Tbk based on Return On Assets (ROA), Gross Profit Margin (GPM) and Net Working Capital (NWC) is in the bad category. While the financial performance of PT. Adaro Energi, Tbk based on the Quick Ratio (QR) is in the good category.